PERAN MEDIASI KEPUASAN KERJA PADA PENGARUH PENDIDIKAN DAN PELATIHAN (DIKLAT), DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA BISMA EIGHT HOTEL DAN VILLA UBUD, BALI - I Made Angga Suarga; Ni Putu Ayu Sintya Saraswati; Ary Wira Andika (VALUES, 2024)
Performance is a work result achieved by a person in carrying out the tasks assigned to him which is based on skill, experience, seriousness and time. To create high employee performance, organizations must be able to provide training to their employees which is accompanied by a disciplined attitude from the employees to carry out their duties so that they can increase their overall productivity and can increase their job satisfaction which ultimately has an impact on their increased performance. This research aims to test and obtain empirical evidence of the mediating role of job satisfaction on the influence of education and training (diklat) and work discipline on employee performance at the Bisma Eight Hotel and Villa. The population in this study were 139 employees who worked at the Bisma Eight Hotel and Villa. The sample in this study was 58 people using the Slovin formula. Data collection uses a questionnaire. The data analysis technique uses SEM-PLS 3.0. The results of the research show that: 1) education and training (diklat) have a positive and significant effect on employee performance, 2) work discipline has a positive and significant effect on employee performance, 3) education and training (training) has a positive and significant effect on job satisfaction, 4 ) work discipline has a positive and significant effect on job satisfaction, 5) job satisfaction has a positive and significant effect on employee performance, 6) job satisfaction is able to be a mediating variable on the effect of training on employee performance, and 7) job satisfaction is able to be a mediating variable on the effect of discipline work on employee performance. Future research can develop this research by using other variables which theoretically have an influence on employee performance.